Note on arithmetical functions and multiples - Stakėnas, Vilius (Lietuvos matematikos rinkinys, 2008)
The existence of the logarithmic and number-theoreticdensitiesof some sets related to arithmetical functions is investigated. The Dirichlet convolution is used for the representation of these functions.